Efficient heat dissipation multilayer ceramic substrate and preparation method thereof
By using alumina and vanadium pentoxide in multi-layer ceramic substrates, pretreatment and optimization of sintering processes, the problem of insufficient fracture toughness of traditional ceramic substrates is solved, and higher fracture toughness and stability are achieved, while maintaining good heat dissipation performance.
Patent Information
- Application Number
- CN202510285993.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
Traditional multi-layer ceramic substrates have low fracture toughness and are prone to brittle fracture when subjected to external forces, which limits their application scenarios where dynamic loads or external forces are susceptible to impact.
Alumina and vanadium pentoxide are used as the main components, and the growth rate and microstructure of alumina grains are regulated by pretreating alumina and optimizing the sintering process to improve the fracture toughness of the substrate.
The fracture toughness of the multi-layer ceramic substrate is significantly improved, its stability and service life under the action of external forces are enhanced, and good heat dissipation performance is maintained.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic substrates, and in particular to a high-efficiency heat dissipation multilayer ceramic substrate and a preparation method thereof. Background Art
[0002] A multilayer ceramic substrate is a three-dimensional ceramic substrate made by printing, laminating, sintering and other processes to form a multilayer ceramic sheet. It integrates functional structures such as through holes. Its core function is to serve as an electrical connection carrier, mechanical support platform and physical protection layer for electronic components, while also acting as a medium for signal transmission and heat dissipation. With its unique advantages, this substrate has been widely used in optical communications, medical equipment, lighting systems, energy management and other fields.
[0003] Traditional multilayer ceramic substrates are usually made of alumina ceramic materials as the main material. Because of its high flatness, it can reduce the contact thermal resistance between the substrate and the load or heat sink to a certain extent. At the same time, it has attracted much attention due to its good heat dissipation ability, chemical stability, antioxidant ability and low production cost. However, among the many performance indicators of multilayer ceramic substrates, fracture toughness is one of the core indicators to measure its reliability. It reflects the ability of multilayer ceramic substrates to resist fracture when subjected to external forces, and is closely related to the stability and service life of multilayer ceramic substrates in practical applications. However, the fracture toughness of alumina multilayer ceramic substrates is low. When subjected to external forces such as impact, vibration or thermal stress, it is easy to cause brittle fracture, cracks or even breakage, which limits it in some application scenarios with dynamic loads or susceptible to external impact. At present, by improving the microstructure of alumina multilayer ceramic substrates, the fracture toughness of alumina ceramic substrates can be improved to a certain extent, for example, by using more advanced sintering technology or by adding a second phase to achieve the purpose of improving the microstructure. In the addition of the second phase, fiber materials are usually introduced to change the intergranular fracture mode of traditional alumina powder, thereby improving the fracture toughness of the alumina multilayer ceramic substrate. However, during the sintering process, the fiber material is easily sintered into one with the ceramic matrix, which limits the improvement of the fracture toughness of the alumina multilayer ceramic substrate.
[0004] In view of this, developing a multilayer ceramic substrate that can significantly improve its fracture toughness is of great significance for expanding its application. Summary of the invention
[0005] The present invention provides a multi-layer ceramic substrate with high efficiency in heat dissipation and a preparation method thereof, which solves the problem of poor fracture toughness of the multi-layer ceramic substrate in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a multi-layer ceramic substrate with high efficiency in heat dissipation, the raw materials of which include the following components in parts by weight: 110 parts of aluminum oxide, 8-16 parts of vanadium pentoxide, 1-3 parts of dispersant, 2-4 parts of sintering aid, 8-12 parts of binder, 0.5-2 parts of plasticizer, 70 parts of water; The aluminum oxide includes aluminum oxide I and aluminum oxide II in a weight ratio of 4 to 9:1; The specific surface area of the aluminum oxide I is 47 to 76 m 2 / g, the specific surface area of the aluminum oxide II is 6.8~8m 2 / g.
[0007] As a further technical solution, the average particle size of the aluminum oxide I and the aluminum oxide II is independently 15 to 50 μm.
[0008] As a further technical solution, the weight ratio of the aluminum oxide to the vanadium pentoxide is 11:1 to 1.4.
[0009] In the present invention, during the sintering process, vanadium pentoxide can be filled into the pores of the grain boundary to a certain extent, thereby enhancing the bonding force between the grains. In addition, the grain growth of aluminum oxide during the sintering process is often faster. The addition of vanadium pentoxide can properly regulate the growth rate of aluminum oxide grains, thereby reducing the influence of the uneven internal structure of the ceramic substrate caused by the large difference in the growth size of aluminum oxide grains, thereby further improving the fracture toughness of the multilayer ceramic substrate. When the weight ratio of aluminum oxide to vanadium pentoxide is 11:1-1.4, the fracture toughness of the multilayer ceramic substrate can be increased to 12.7-13.0. When the weight ratio of aluminum oxide to vanadium pentoxide is outside the range of 11:1~1.4, the effect of improving the fracture toughness of the multilayer ceramic substrate becomes worse. It can be seen that for aluminum oxide, too much or too little vanadium pentoxide content will limit the improvement of the fracture toughness of the multilayer ceramic substrate.
[0010] As a further technical solution, the alumina is pretreated alumina, and the raw materials of the pretreated alumina include alumina and polysaccharide in a weight ratio of 25:1-5.
[0011] As a further technical solution, the method for preparing the pretreated alumina comprises the following steps: A1. After adding polysaccharide to water, stir for the first time, add alumina, stir for the second time, and dry to obtain a premix; A2. After ball milling the premixture, sintering is performed to obtain pretreated alumina.
[0012] As a further technical solution, the weight ratio of alumina to polysaccharide is 25:2~3.
[0013] As a further technical solution, the polysaccharide includes one or more of chitosan, dextran, and starch, preferably chitosan and starch.
[0014] As a further technical solution, the weight ratio of chitosan to starch is 4:1.
[0015] As a further technical solution, in step A1, the speed of the first stirring and the second stirring are independently 500-700 rpm, and the time is 1-3 hours.
[0016] As a further technical solution, in step A2, the ball milling speed is 600-800 rpm and the time is 2-3 h.
[0017] As a further technical solution, in step A2, the sintering is divided into a first sintering and a second sintering; During the first sintering, the sintering atmosphere is air, the temperature is 550-650°C, and the time is 2-4 hours; During the second sintering, the sintering atmosphere is nitrogen, the temperature is 1450-1550°C, and the time is 0.5-1.5h; The nitrogen gas flow rate is 15-20 L / min.
[0018] In the present invention, polysaccharides are first used to treat alumina, and the content ratio of polysaccharides and alumina is reasonably adjusted so that the alumina is combined together during the pretreatment process. Through the subsequent sintering treatment, the microstructure of alumina can be assisted in regulating, while being beneficial to the bonding effect between alumina particles of different crystal forms, making the bonding between the grains tighter, thereby improving the bending strength of the multilayer ceramic substrate.
[0019] In the present invention, sintering is divided into a first sintering and a second sintering. The first sintering is carried out in an air atmosphere at a relatively low temperature of 550-650°C. This process mainly plays a pretreatment role of polysaccharide on alumina, so that the alumina particles begin to undergo initial crystal growth, laying the foundation for subsequent high-temperature sintering; the second sintering is carried out in a nitrogen atmosphere at a relatively high temperature of 1450-1550°C. This process mainly further improves the stability of the alumina crystal structure, can further sinter and densify, and can obtain alumina with high strength and good stability, thereby further improving the bending strength of the multilayer ceramic substrate.
[0020] As a further technical solution, the sintering aid is one or more of Y2O3, YF3, and B2O3; The binder is one or two of polyvinyl butyral and hydroxypropyl methylcellulose; The plasticizer is one or more of polyethylene glycol, dioctyl phthalate, and polypropylene alcohol; The dispersant is one or more of stearic acid, polyacrylic acid and polymethacrylic acid.
[0021] As a further technical solution, when the sintering aids are Y2O3 and B2O3, the weight ratio of Y2O3 to B2O3 is 3:1.
[0022] When the sintering aids are Y2O3 and B2O3 in a weight ratio of 3:1, the sintering temperature of alumina can be effectively reduced, making the microstructure of the ceramic more uniform, thereby reducing the defects of cracks in ceramic materials in an environment with rapid temperature changes. Under the action of vanadium pentoxide and other additives, the fracture toughness and mechanical properties of the multilayer ceramic substrate are further improved.
[0023] In the process of preparing multilayer ceramic substrates, alumina itself is difficult to shape, and the addition of binders can directly give the alumina ceramic material a certain viscosity, thereby ensuring the integrity and stability of the final multilayer ceramic substrate; the addition of plasticizers can increase the compatibility between alumina powder and binders, enabling the binder to better play a bonding role and reduce surface defects, thereby improving the comprehensive performance of the multilayer ceramic substrate; the addition of dispersants, such as stearic acid, polyacrylic acid, and polymethacrylic acid, can be adsorbed on the surface of alumina particles, so that the alumina particles are evenly dispersed in the slurry, making the particle distribution inside the ceramic substrate more uniform.
[0024] The present invention also proposes a method for preparing a high-efficiency heat dissipation multilayer ceramic substrate, comprising the following steps: S1. After mixing the remaining components except the binder, the binder is added and mixed for a second time to obtain a slurry; S2, subjecting the slurry to degassing, tape casting and drying to obtain a green porcelain sheet; S3, subjecting the raw ceramic sheets to punching, hole filling, surface printing, lamination, pressing, and thermal cutting processes, and then to co-firing and cooling to obtain the high-efficiency heat dissipation multilayer ceramic substrate.
[0025] As a further technical solution, in step S1, during the first mixing, the ball milling speed is 300-400 rpm, and the time is 2-3 h; during the second mixing, the ball milling speed is 500-700 rpm, and the time is 1.5-2.5 h. As a further technical solution, in step S3, during the punching, the punching pressure is 0.4-0.6 MPa.
[0026] As a further technical solution, in step S3, circular microholes with a diameter of 0.1-0.2 mm can be formed during the punching.
[0027] As a further technical solution, in step S3, the raw material for surface printing is tungsten slurry, and the thickness of the tungsten slurry is 10-18 μm.
[0028] As a further technical solution, in step S3, the number of layers of the laminate is 45-55 layers, the temperature of the laminate is 40-60° C., and the pressure of the laminate is 5-9 MPa.
[0029] As a further technical solution, in step S3, the pressure during the pressing is 15-20 MPa.
[0030] As a further technical solution, in step S3, during the co-firing, the temperature is 950-1050° C. and the time is 20-40 min.
[0031] The working principle and beneficial effects of the present invention are: In the present invention, a multilayer ceramic substrate is prepared by using alumina as a base material, combining vanadium pentoxide, a dispersant, a sintering aid, a binder, and a plasticizer to obtain a dense and stable multilayer ceramic substrate having good fracture toughness; wherein the alumina includes alumina I and alumina II with different specific surface areas, and the specific surface area of alumina I is 47-76 g / cm 3 The specific surface area of aluminum oxide II is 6.8~8g / cm 3 During the sintering process, the two types of aluminum oxide play a role of restraining each other, which can make the growth rate of aluminum oxide grains in a moderate state, and make the internal structure of the ceramic substrate uniform and dense. When the multilayer ceramic substrate is subjected to external force, the particle gaps formed by aluminum oxide I and aluminum oxide II are evenly distributed, which can reduce the possibility of stress concentration, thereby reducing the possibility of crack propagation and improving the fracture toughness of the multilayer ceramic substrate. By optimizing the content ratio of aluminum oxide I and aluminum oxide II, when the weight ratio of aluminum oxide I and aluminum oxide II is 4~9:1, the effect of improving the fracture toughness of the multilayer ceramic substrate is optimal. In addition, the addition of vanadium pentoxide can also improve the fracture toughness of the multilayer ceramic substrate to a certain extent. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following examples and comparative examples, the average particle size of aluminum oxide I and aluminum oxide II is 25 μm; the average particle size of vanadium pentoxide is 38 μm; the viscosity of hydroxypropyl methylcellulose is 100,000 mPa·s; the model of polyethylene glycol is PEG-1000; chitosan has a deacetylation degree of 90% and a weight-average molecular weight of 20,000; and the starch is corn starch, and the active ingredient content is 98%.
[0034] Example 1 A high-efficiency heat dissipation multilayer ceramic substrate, the raw materials include the following components in parts by weight: 110 parts of aluminum oxide, 8 parts of vanadium pentoxide, 1 part of stearic acid, 1.5 parts of Y2O3, 0.5 parts of B2O3, 8 parts of hydroxypropyl methylcellulose, 0.5 parts of polyethylene glycol, 70 parts of water; The alumina includes alumina I and alumina II in a weight ratio of 4:1; The specific surface area of alumina I is 47m 2 / g, the specific surface area of alumina II is 6.8m 2 / g; A method for preparing a multilayer ceramic substrate with high efficiency heat dissipation comprises the following steps: S1. After mixing the remaining components except hydroxypropyl methylcellulose at a ball milling speed of 300 rpm for 3 h, hydroxypropyl methylcellulose was added, and mixed at a ball milling speed of 500 rpm for 2.5 h to obtain a slurry; S2, removing bubbles, tape casting and drying the slurry to obtain a green porcelain sheet; S3. Punch the raw ceramic sheets at a punching pressure of 0.4 MPa to form circular micropores with a diameter of 0.1 mm, fill the holes, print tungsten slurry with a thickness of 15 μm on the surface, stack 45 layers of raw ceramic sheets at 40°C and 5 MPa, press them at 15 MPa, cut them, co-fire them at 950°C for 40 minutes, and cool them to obtain a multi-layer ceramic substrate with high efficiency heat dissipation.
[0035] Example 2 A high-efficiency heat dissipation multilayer ceramic substrate, the raw materials include the following components in parts by weight: 110 parts of aluminum oxide, 16 parts of vanadium pentoxide, 2 parts of stearic acid, 2.25 parts of Y2O3, 0.75 parts of B2O3, 10 parts of hydroxypropyl methylcellulose, 1.5 parts of polyethylene glycol, 70 parts of water; The alumina includes alumina I and alumina II in a weight ratio of 6:1; The specific surface area of alumina I is 47m 2 / g, the specific surface area of alumina II is 6.8m 2 / g; A method for preparing a multilayer ceramic substrate with high efficiency heat dissipation comprises the following steps: S1. After mixing the remaining components except hydroxypropyl methylcellulose at a ball milling speed of 350 rpm for 2.5 h, hydroxypropyl methylcellulose was added, and the mixture was mixed at a ball milling speed of 600 rpm for 2 h to obtain a slurry; S2, removing bubbles, tape casting and drying the slurry to obtain a green porcelain sheet; S3. Punch the raw ceramic sheets at a punching pressure of 0.5MPa to form circular micropores with a diameter of 0.14mm, fill the holes, print tungsten slurry with a thickness of 15μm on the surface, stack 50 layers of raw ceramic sheets at 50℃ and 7MPa, press them at 18MPa, cut them, co-fire them at 990℃ for 30min, and cool them to obtain a multi-layer ceramic substrate with high efficiency heat dissipation.
[0036] Example 3 A high-efficiency heat dissipation multilayer ceramic substrate, the raw materials include the following components in parts by weight: 110 parts of aluminum oxide, 16 parts of vanadium pentoxide, 3 parts of stearic acid, 3 parts of Y2O3, 1 part of B2O3, 12 parts of hydroxypropyl methylcellulose, 2 parts of polyethylene glycol, 70 parts of water; The alumina includes alumina I and alumina II in a weight ratio of 9:1; The specific surface area of alumina I is 76 m 2 / g, the specific surface area of alumina II is 8m 2 / g; A method for preparing a multilayer ceramic substrate with high efficiency heat dissipation comprises the following steps: S1. After mixing the remaining components except hydroxypropyl methylcellulose at a ball milling speed of 400 rpm for 2 h, hydroxypropyl methylcellulose was added, and the mixture was mixed at a ball milling speed of 700 rpm for 1.5 h to obtain a slurry; S2, removing bubbles, tape casting and drying the slurry to obtain a green porcelain sheet; S3. Punch the raw ceramic sheets at a punching pressure of 0.6MPa to form circular micropores with a diameter of 0.2mm, fill the holes, print tungsten slurry with a thickness of 15μm on the surface, stack 55 layers of raw ceramic sheets at 60℃ and 9MPa, press them at 20MPa, cut them, co-fire them at 1050℃ for 20min, and cool them to obtain a multi-layer ceramic substrate with high efficiency heat dissipation.
[0037] Example 4 The only difference between this embodiment and Embodiment 1 is that, in this embodiment, the aluminum oxide includes aluminum oxide I and aluminum oxide II in a weight ratio of 9:1.
[0038] Example 5 The only difference between this embodiment and embodiment 1 is that in this embodiment, the amount of vanadium pentoxide added is 16 parts.
[0039] Example 6 The only difference between this embodiment and embodiment 1 is that in this embodiment, the amount of vanadium pentoxide added is 10 parts.
[0040] Example 7 The only difference between this embodiment and embodiment 1 is that in this embodiment, the amount of vanadium pentoxide added is 14 parts.
[0041] Example 8 The difference between this embodiment and embodiment 7 is that, in this embodiment, the aluminum oxide is pretreated aluminum oxide, and the preparation method of the pretreated aluminum oxide includes the following steps: A1. After adding 4.4 parts of polysaccharide (wherein the weight ratio of chitosan to starch is 4:1) to 100 parts of water, stirring at 500 rpm for 3 hours, adding 110 parts of alumina (wherein the weight ratio of alumina I to alumina II is 4:1), stirring at 500 rpm for 3 hours, and drying to obtain a premix; A2. The premixture was ball-milled at 600 rpm for 3 h, sintered at 550° C. in an air atmosphere for 4 h, and then sintered at 1450° C. in a nitrogen atmosphere with a gas flow rate of 15 L / min for 1.5 h to obtain pretreated alumina.
[0042] Example 9 The only difference between this embodiment and embodiment 8 is that in the preparation process of the pretreated alumina in this embodiment, the amount of polysaccharide added is 22 parts, wherein the weight ratio of chitosan to starch is 4:1.
[0043] Example 10 The only difference between this embodiment and embodiment 8 is that in the preparation process of the pretreated alumina in this embodiment, the amount of polysaccharide added is 8.8 parts, wherein the weight ratio of chitosan to starch is 4:1.
[0044] Embodiment 11 The only difference between this embodiment and embodiment 8 is that in the preparation process of the pretreated alumina in this embodiment, the amount of polysaccharide added is 13.2 parts, wherein the weight ratio of chitosan to starch is 4:1.
[0045] Example 12 The difference between this embodiment and embodiment 11 is that, in this embodiment, the method for preparing the pretreated aluminum oxide comprises the following steps: A1. Add 13.2 parts of polysaccharide (wherein the weight ratio of chitosan to starch is 4:1) to 100 parts of water, stir at 700 rpm for 1 hour, add 110 parts of alumina (wherein the weight ratio of alumina I to alumina II is 4:1), stir at 700 rpm for 1 hour, and dry to obtain a premix; A2. The premixture was ball-milled at 800 rpm for 2 h, sintered at 650° C. in an air atmosphere for 2 h, and then sintered at 1550° C. in a nitrogen atmosphere with a gas flow rate of 20 L / min for 0.5 h to obtain pretreated alumina.
[0046] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the weight ratio of aluminum oxide I to aluminum oxide II is 1:1.
[0047] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the weight ratio of aluminum oxide I to aluminum oxide II is 10:1.
[0048] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, aluminum oxide I is replaced by an equal amount of aluminum oxide II.
[0049] Comparative Example 4 The only difference between this comparative example and Example 1 is that in this comparative example, aluminum oxide II is replaced by an equal amount of aluminum oxide I.
[0050] Comparative Example 5 The difference between this comparative example and Example 1 is that in this comparative example, the specific surface area of aluminum oxide I is 39 m 2 / g, the specific surface area of alumina II is 5m 2 / g.
[0051] Comparative Example 6 The difference between this comparative example and Example 1 is that in this comparative example, the specific surface area of aluminum oxide I is 100 m 2 / g, the specific surface area of alumina II is 11m 2 / g.
[0052] Comparative Example 7 The only difference between this comparative example and Example 1 is that in this comparative example, vanadium pentoxide is replaced by an equal amount of zirconium oxide.
[0053] Comparative Example 8 The only difference between this comparative example and Example 1 is that in this comparative example, vanadium pentoxide is not added.
[0054] Test Example 1 The fracture toughness of the multilayer ceramic substrates prepared in Examples 1 to 7 and Comparative Examples 1 to 8 was tested according to the method in GB / T 23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method", and the test results are shown in Table 1: Table 1 Fracture toughness test results of Examples 1 to 7 and Comparative Examples 1 to 8
[0055] It can be seen from Table 1 that compared with Comparative Examples 1 to 4, the fracture toughness of the multilayer ceramic substrates prepared in Examples 1 to 6 is significantly improved, indicating that the aluminum oxide includes aluminum oxide I and aluminum oxide II, and the specific surface area of aluminum oxide I is 47 to 76 m 2 / g, the specific surface area of alumina II is 6.8~8m 2 / g, by using two different aluminum oxides in combination and adjusting the weight ratio of aluminum oxide I to aluminum oxide II to 4-9:1, the fracture toughness of the multilayer ceramic substrate can be improved. In addition, compared with comparative examples 7-8, the fracture toughness of the multilayer ceramic substrates obtained in Examples 1 and 5-7 is improved, indicating that when vanadium pentoxide and aluminum oxide are present at the same time, the fracture toughness of the multilayer ceramic substrate can also be improved.
[0056] Test Example 2 The multilayer ceramic substrates prepared in Examples 7 to 12 were tested for bending strength according to the test method specified in GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", wherein the test method adopted three-point bending. The test results are shown in Table 2: Table 2 Bending strength test results of Examples 7 to 12
[0057] It can be seen from Table 2 that the bending strength of the multilayer ceramic substrates prepared in Examples 8 to 12 is higher than that of the multilayer ceramic substrate prepared in Example 7, indicating that the bending strength of the multilayer ceramic substrate can be improved after pretreating alumina with polysaccharide.
[0058] Test Example 3 The thermal conductivity of the multilayer ceramic substrates prepared in Examples 1 to 3 was measured according to GB / T 32064-2015 "Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials by Transient Planar Heat Source", and the test results are shown in Table 3: Table 3 Thermal conductivity test results of Examples 1 to 3
[0059] The thermal conductivity of the multilayer ceramic substrates prepared in Examples 1 to 3 is in the range of 34.7 to 38.1 W / (m·k), and has a good heat dissipation effect.
[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-efficiency heat dissipation multilayer ceramic substrate, characterized in that: The raw materials include the following components in parts by weight: 110 parts of aluminum oxide, 8-16 parts of vanadium pentoxide, 1-3 parts of dispersant, 2-4 parts of sintering aid, 8-12 parts of binder, 0.5-2 parts of plasticizer, 70 parts of water; The aluminum oxide includes aluminum oxide I and aluminum oxide II in a weight ratio of 4 to 9:1; The specific surface area of the aluminum oxide I is 47 to 76 m 2 / g, the specific surface area of the aluminum oxide II is 6.8~8m 2 / g.
2. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 1, characterized in that: The weight ratio of the aluminum oxide to the vanadium pentoxide is 11:1-1.
4.
3. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 1, characterized in that: The alumina is pretreated alumina, and the raw materials of the pretreated alumina include alumina and polysaccharide in a weight ratio of 25:1-5.
4. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 3, characterized in that: The method for preparing the pretreated aluminum oxide comprises the following steps: A1. After adding polysaccharide to water, stir for the first time, add alumina, stir for the second time, and dry to obtain a premix; A2. After ball milling the premixture, sintering is performed to obtain pretreated alumina.
5. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 3, characterized in that: The weight ratio of the alumina to the polysaccharide is 25:2-3.
6. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 3, characterized in that: The polysaccharide includes one or more of chitosan, dextran and starch.
7. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 4, characterized in that: In step A2, the sintering is divided into a first sintering and a second sintering; During the first sintering, the sintering atmosphere is air, the temperature is 550-650°C, and the time is 2-4 hours; During the second sintering, the sintering atmosphere is nitrogen, the temperature is 1450-1550°C, and the time is 0.5-1.5h; The nitrogen gas flow rate is 15-20 L / min.
8. The high-efficiency heat dissipation multilayer ceramic substrate according to claim 1, characterized in that: The sintering aid is one or more of Y2O3, YF3, and B2O3; The binder is one or two of polyvinyl butyral and hydroxypropyl methylcellulose; The plasticizer is one or more of polyethylene glycol, dioctyl phthalate, and polypropylene alcohol; The dispersant is one or more of stearic acid, polyacrylic acid and polymethacrylic acid.
9. The method for preparing a high-efficiency heat dissipation multilayer ceramic substrate according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. After mixing the remaining components except the binder, the binder is added and mixed for a second time to obtain a slurry; S2, subjecting the slurry to degassing, tape casting and drying to obtain a green porcelain sheet; S3, subjecting the raw ceramic sheets to punching, hole filling, surface printing, lamination, pressing, and thermal cutting processes, and then to co-firing and cooling to obtain the high-efficiency heat dissipation multilayer ceramic substrate.
10. The method for preparing a high-efficiency heat dissipation multilayer ceramic substrate according to claim 9, characterized in that: In step S1, during the first mixing, the ball milling speed is 300-400 rpm, and the time is 2-3 h; during the second mixing, the ball milling speed is 500-700 rpm, and the time is 1.5-2.5 h.
Citation Information
Patent Citations
Alumina ceramic with high heat dissipation efficiency and preparation method thereof
CN102731070A
Organic ceramic substrate composition, organic ceramic substrate, and copper-clad plate
CN106365507A
Alumina-based ceramic slurry and preparation method of ceramic core thereof
CN112174637A
Alumina ceramic substrate and preparation method thereof
CN118894717A
Manufacture of ceramic substrate
JP1991041792A
Cited By
Alumina multilayer ceramic substrate and preparation method thereof
CN120097716A
Aluminum oxide multi-layer ceramic substrate and its preparation method
CN120097716B
High-fracture-resistance aluminum oxide multilayer ceramic substrate and preparation method thereof
CN120554099A